THE ROLE OF CORPORATE TRANSPARENCY IN MODERATING THE INFLUENCE OF LEVERAGE AND TAX AVOIDANCE ON FIRM VALUE IN THE REAL ESTATE AND PROPERTY SECTOR IN INDONESIA - Sohono, Suhono; Putri, Ajeng Eka; Akbar M, Nahruddien; Mahpudin, Endang; Sulastri, Eva Maria (Universitas Padjadjaran, 2024)
Increasing scrutiny on the impact of leverage and tax evasion on business value, particularly in the real estate and property sectors, has become a significant phenomenon. Incorporating corporate transparency as a moderating variable, this research aims to provide empirical data on these critical financial dynamics. The population comprises companies listed on the Indonesia Stock Exchange during the 2019–2021 period, with a sample of ten companies selected based on pre-established criteria. Data collection involved quantitative methods, including descriptive statistical analysis, multiple regression, moderation regression, and traditional assumption tests. Hypothesis testing was conducted using both concurrent and partial experiments. The findings reveal significant relationships between firm value and tax avoidance, leverage and firm value, and business transparency. Notably, while corporate transparency effectively moderates the relationship between leverage and firm value, it does not have the same effect on the relationship between tax avoidance and firm value. These results emphasize the importance of leveraging transparency to enhance business value, suggesting that companies should prioritize transparent practices to mitigate the adverse effects of tax evasion. Theoretically, this research contributes to the understanding of corporate finance by illustrating how corporate transparency influences the dynamics between leverage, tax avoidance, and firm value. Practically, it highlights the necessity for property and real estate companies to adopt more transparent financial practices to foster investor confidence and enhance market value. Future research could explore additional factors influencing these relationships for deeper insights into corporate finance dynamics in Indonesia.